From Theory to Practice in Programming for Student-Athletes - Foster, Tanya R. (My University, 1986)
This paper contends that program development for student-athletes must begin with a theoretical base if the program is to meet the psychological needs of the student-athletes and earn the respect of administrators and academicians. Theory combined with a program implementation model facilitates both the creation and evaluation of a program. A blueprint for one program developed via this method is provided. The article reviews some historical background and how athletic counselors should be more than eligibility counselors. It discusses the foundations of Purdue's program at its infancy.
Keywords: theory; academic support